Surface and degradation properties of thermoplastic blends from albumin and zein‐based plastics. Issue 13 (25th November 2016) - Jones, Alexander; Sharma, Suraj
ABSTRACT: The use of traditional petroleum‐based thermoplastics in food packaging applications pose an environmental hazard, as their lack of biodegradability creates waste that environmental systems are unable to cope with. To address this issue, the investigation of surface, biodegradation, and water solubility properties of the albumin and zein thermoplastic blends plasticized with glycerol and mixed with varying amounts of low‐density polyethylene (LDPE) is conducted. When subjected to soil burial, albumin as a bioplastic completely biodegrades within two months, while a zein‐based bioplastic is more resilient to attacks from microbes within the soil (4.34% of intial mass remains). If albumin and zein proteins are used in the production of thermoplastics in tandem with LDPE, it could be possible to produce a plastic that will naturally biodegrade over time, decreasing the environmental impact of the use of thermoplastics in medical and food packaging applications. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44646. Abstract :